1992
DOI: 10.1111/j.1476-5381.1992.tb14493.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that 5‐HT2receptor activation decreases noradrenaline release in rat hippocampusin vivo

Abstract: 1 Recent electrophysiological studies have shown that 5-HT215-HTlc receptor agonists inhibit the electrical activity of noradrenergic neurones in the rat locus coeruleus. Here we examine the effect of various agonists and antagonists of 5-HT2/5-HT,c receptors on noradrenaline release in hippocampus of anaesthetized rats using microdialysis.2 Subcutaneous administration of the 5-HT2/5-HTc receptor agonist, 1-(2,5-dimethoxy-4-iodophenyl) -2-aminopropane (DOI: 0.2 and 0.5 mg kg-'), caused a marked decrease (50% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…For the 5-HT 2 receptor modulating NA release in the rat hippocampus, this effect is indirect as well and the location of the receptor is also by no means clear (Done and Sharp, 1992). These restrictions are valid because the respective microdialysis study in anesthetized rats was almost exclusively based on subcutaneous injection of nonselective 5-HT 2 receptor ligands.…”
Section: Function and Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 5-HT 2 receptor modulating NA release in the rat hippocampus, this effect is indirect as well and the location of the receptor is also by no means clear (Done and Sharp, 1992). These restrictions are valid because the respective microdialysis study in anesthetized rats was almost exclusively based on subcutaneous injection of nonselective 5-HT 2 receptor ligands.…”
Section: Function and Locationmentioning
confidence: 99%
“…In awake rats, the 5-HT 2 receptor antagonists ritanserin and ICI 170,809 given alone increased NA release, suggesting tonic activation of the 5-HT 2 receptors (Done and Sharp, 1994). The inhibition of NA release in the hippocampus (Done and Sharp, 1992) was suggested to be directly related to a decrease in the firing rate of noradrenergic neurons in the locus coeruleus in response to systemic administration of DOB, DOM, and quipazine, an effect sensitive to blockade by 5-HT 2 receptor antagonists Gorea and Adrien, 1988). A direct inhibitory action of the 5-HT 2 receptor ligands on the noradrenergic nerve terminals of the hippocampus was excluded in preliminary experiments by the failure of DOI, applied locally via the dialysis probe, to modify NA release.…”
Section: Function and Locationmentioning
confidence: 99%
“…The participation of 5-HT in the control of blood pressure (Cohen, 1984;Grading et al, 1985;Saxena et al, 1987; Dabire, 1990) and the modulation of cardiac and vascular sympathetic transmission has also been demonstrated. For this modulation, potentiating and inhibitory actions have been proposed, however in both cases there is a disparity between mechanisms postulated to account for such actions (Fozard & Mwaluko, 1976;Fozard, 1984b;Coote et al, 1987;Docherty, 1988;Bom et al, 1989;Shepheard et al, 1991;Done & Sharp, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…They reported the inhibitory infl uence of the 5-HT agonists on the NA synthesis in this nucleus [ 13 ] . In addition, the latter study suggested that the 5-HT 2 receptors mediate the 5-HT inhibitory eff ect on the NA synthesis [ 13 ] . Duloxetine is also a 5-HT and NA reuptake inhibitor [ 14 ] that inhibits the 5-HT reuptake 5-fold greater than the NA [ 15 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Done, et. al. reported that the 5-HT induces the inhibitory eff ect on the LC hyperactivity that is mediated by the 5-HT 2 receptors [ 13 ] . Moreover, antidepressant drugs with the 5-HT and/or the NA reuptake inhibition activity are frequently used for the treatment of pains related to postherpetic neuralgia, diabetic neuropathy, and fi bromyalgia [ 43 , 44 ] .…”
Section: Figmentioning
confidence: 99%